Development of Powtoon Video Media in Geography Subjects - Detti Wijayanti; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2021)
The teaching and learning process is a process of reciprocal interaction between students and teachers and between students to achieve learning objectives. This research was conducted at SMA Negeri 1 Sungai Rumbai using research and development methods or often called Research and Development (R&D). The results of the research obtained are that the Powtoon learning video learning media is declared very feasible after analyzing data processing using Microsoft Excel so that the total score is 383 with a mean level of 4.89 and a percentage level of 98% with the predicate